The radio interview - Thompson, Bronwyn; Jasek, Richard; Lee, Colin; First Light Video Publishing; Australian Film and Television School (Australia : AFTRS, 1991)
Presents the process of conducting an interview, including preinterview research and determining equipment needs
Title from title screen
Executive producer, Jason Wheatley ; music, James D'Arcy
Presenter: Mike Broadhurst and Alan Wheatley
Keywords: Interviewing on radio; Interviews